APPLICATION OF LAPLACE-DIFFERENTIAL TRANSFORM METHOD TO TRANSPORT PROBLEMS IN POROUS MEDIA - ADEYEMI TEMITAYO SHERIFF; OJO IBUKUN JOEL (International Journal of Innovations in Engineering Research and Technology, 2021)
Over the years, several solutions to the problems of porous media flow have been developed. However, most of these solutions are very complex because they involve infinite summation of Bessel, Exponential and some other complex functions. As a result of their complexities, they often require lots of approximations (based on some assumptions) for most practical Engineering applications and this in turn reduces the accuracy of their real life applications. Therefore, this paper presents a novel method (combined Laplace and Differential transform) suitable for obtaining very simple and excellently accurate solutions to equations that governs fluid transport in porous media. The results obtained testify to the effectiveness, efficiency and conveniency of the proposed approach.